El Socialismo del Siglo XXI: ¿una nueva o vieja alternativa para América Latina globalizada? - González-Ramírez, Fabián (2014)
This essay aims to discuss whether the 21st. CenturySocialism approach can be a new and feasibleoption for Latin America in the context ofglobalization. Such question lays answers thatare still distant and complicated but this end varioustheoretical positions are discussed focusing onthe New Social Movements, as an alternative of theGlobal South.